Cobalt hydroxide-black phosphorus nanosheets: A superior electrocatalyst for electrochemical oxygen evolution. (20th February 2019) - Li, Yejun; Liao, Chengan; Tang, Kewei; Zhang, Ning; Qi, Weihong; Xie, Haipeng; He, Jun; Yin, Kai; Gao, Yongli; Wang, Chundong
Abstract: Black phosphorus (BP), a new rediscovered 2-dimensional material, has gained enormous attention in the field of electrocatalysis, particularly for oxygen evolution reactions. However, its easily being oxidized nature and the bulk crystal structure restricts sufficient active sites, which severely hinders its potential applications in catalysis. Herein, BP nanosheets are prepared and deposited with Co(OH)2 nanosheets to construct the Co(OH)2 /BP interfaces. Owing to the high Fermi level of Co(OH)2 than that of BP, the electrons are transferred initiatively from Co(OH)2 to BP, affording remarkable oxygen evolution reaction performance with an overpotential of 276 mV at a current density of 10 mA cm −2 . Moreover, the potentiostatic tests present decent electrocatalytic stability of the synthesized Co(OH)2 /BP nanosheets. It is further anticipated that engineering the interface towards manipulating the charge density on BP surface and/or interface by depositing other kind of catalysts could be a straightforward strategy to design outstanding hybrid electrocatalysts. Graphical abstract: Image 1